Late Quaternary variability of Mediterranean Outflow Water from radiogenic Nd and Pb isotopes - Stumpf, Roland; Frank, Martin; Schönfeld, Joachim; Haley, Brian A. (Quaternary Science Reviews, 2010)
Mediterranean Outflow Water (MOW) is characterised by higher temperatures and salinities than other ambient water masses. MOW spreads at water depths between 500 and 1500 m in the eastern North Atlantic and has been a source of salinity for the Atlantic Meridional Overturning Circulation in the North Atlantic. We used high-resolution Nd and Pb isotope records of past ambient seawater obtained from authigenic ferromanganese coatings of sediments in three gravity cores at 577, 1745 and 1974 m water depth in the Gulf of Cadiz and along the Portuguese margin complemented by a selection of surface sediments to reconstruct the extent and pathways of MOWover the past 23 000 years. The surface and downcore Nd isotope data from all water depths exhibit only a very small variability close to the present day composition of MOWbut do not reflect the present day Nd isotopic stratification of the water column as determined from a nearby open ocean hydrographic station. In contrast, the Pb isotope records show significant and systematic variations, which provide evidence for a significantly different pattern of the MOW pathways between 20 000 and 12 000 years ago compared with the subsequent period of time.